SYNTHESIS AND ANTIOXIDANT ACTIVITY OF A NEW 4-AMINOCOUMARIN DERIVATIVE - Ristić, Novica; Radulović, Niko; Dekić, Biljana; Ristić, Milenko; Dekić, Vidoslav (Bulletin of Natural Sciences Research, 2018)
Synthesis, spectral characterization, and evaluation of in vitro antioxidant activity of a new coumarin derivative, 4-((1,3,4-thiadiazol-2-yl)amino)-3-nitro-2H-chromene-2-one, are described. The synthesis of the new product was performed in three reaction steps, with a good overall yield (78%). The structure was corroborated by detailed spectral analysis, including the 1D and 2D NMR experiments (1H- and 13C NMR; 1H-1H COSY, NOESY, HSQC, and HMBC). The in vitro antioxidant activity was evaluated using the DPPH test. The synthesized compound possesses a good free-radical scavenging activity, IC50=596.7±0.3 μg/ml, and can serve as a model for the synthesis of similar compounds with promising antioxidant effects.